Mesopotamian Buffaloes (The Origin) - Alsaedy, Jabbar Khliaf Makassar (Journal of Buffalo Science, 2014)
The aim of this study to throw light on Iraqi Buffalo origin, comparing between past archeological theories based on ivory materials and cylindrical seals findings in Mesopotamia and recent molecular biological studies that based on DNA data. The highest population density found in Mesopotamian Marshlands between three southern governorates (Basrah, The-qar and Missan), respectively which represented the home tract of buffalo and their typical breeders in Iraq, locally named Ma"dan, well known by their traditional community, and characteristic accent, mainly raising buffalo for production of famous dairy thick butter cream, widely consumed by Iraqis at breakfast, named (GAYMER). There is no justification to classify Iraqi buffaloes to a distinct breed, we have many phenotypes from black, piebald to albinoid, with traditional raising system. There is no registration of cross breeding, only interbreeding, but latest country Karyotyping survey and body dimensions revealed that our buffaloes were from reverine type in most populations with large size and have good potentials for milk production. There have been numerous archeological theories around world based on cylindrical seals and archeological materials in determining the origin of buffalo in Mesopotamia and Indus Valley. Developing in molecular genetics studies will appeared to throw light on these archeological evidences, there are three recent DNA basis studies, the most updated Microsatellites markers Iraqi study [1] showed that our buffaloes were originated in Iraq, not imported from India, while the two other studies [2, 3] support the theory that Mesopotamian buffaloes were brought to Iraq from the Indian subcontinent before thousands of years and their breeders (MA’’DAN) from Marsh Arabs are descendants of the population Sumerians principals from the region. According to archeological remains referring to buffalo raising in Mesopotamia before Christ confirming by recent Iraqi molecular studies, these updated data should leading us to register our buffalo as dependant breed in riverine group under the name of (Mesopotamian Buffalo) the home tract that had been raising, with achieving all tools to upgrading and protecting this old National Genetic resource all around country. We need more phylogenic studies should be achieved on Iraqi buffaloes for confirming when and where originated and domestication was happened. Still open question?